Private Vs Public School in the Present Scenario of Basic Education-A Case Study of Barasat Municipality, North 24 Parganas - Mondal, Pijus Kanti; Basak, Kuntal Kumar (International Journal of Scientific Research and Management (IJSRM), 2017)
This paper tries to evaluate the comparison between private and public schools at the primary stage inBarasat (M), N 24 Parganas, and West Bengal, India.20 private and public, primary schools have beenselected out of 91 school from the whole Municipality and the comparison is made on the basis of thethree main parameters, those are infrastructure, quality of education and quality of teaching staff. After theintense survey it is revealed that infrastructure and education in a public primary school is so poor thatthere is need of a huge change to make it fit to participate in competition against private schools. The mainproblems in private primary schools are related with teaching. At the end it can be said that the qualitativedecline in public schools has accelerated mushroom growth in private schools with huge studentsstreaming towards the private school.